DILEMA KEPEMIMPINAN PEREMPUAN DALAM ISLAM - Ida Novianti (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Until now, there is a dilemma about woman leadership in Islam. In one side, there is a belief that the best woman activity isbeing home, take care her husband and children, cooking, cleaning up, and other activity that have domestic character. At the other side,today’s woman demanded to play active role outside home. Patriarchal understanding and culture that dominant at that era still affectposition about woman leadership in Islamic thought discourse, not surprising if their thought’s product inclined to man interest. However,today’s woman have broad opportunity to have role on every domain, include became a leader. This is perfectly appropriate with Islamicteaching because al-Qur’an did not differentiate human except his/her deed